Urban Sufisme dan Urban Salafi pada Era Digital - Kartika; Thalib, Abdullah; Amri, Muh. (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The digital era has brought about major changes in the social, cultural, and religious order of society, including in religious practices and thoughts. Amidst these dynamics, Sufism and Salafi as two major schools of thought in Islam face new complex challenges and opportunities. This study aims to investigate how the two schools adapt to social, cultural, and technological changes in the context of a modern, digitalized urban setting. Using qualitative research methods based on text analysis and participant observation, this study explores patterns and themes that emerge in the interaction of these two schools with urban society and digital media. The results show that Sufism utilizes digital technology to expand the reach of its teachings globally and create a strong virtual community, despite facing challenges related to authenticity and internal polarization. Meanwhile, Salafi focuses on consistency with the pure teachings of Islam through educational institutions, da'wah centers, and selective use of social media, despite often facing negative stigma and challenges of social adaptation. This study concludes that the adaptation of Sufism and Salafi reflects the dynamic religious transformation in the contemporary era, while providing strategic insights to support social harmony and religious integration in a complex urban society.